Acupuncture versus sham acupuncture and usual care for Antiandrogen-Induced hot fLashes in prostate cancer (AVAIL): study protocol for a randomized clinical trial - Zongshi Qin; Zhiwei Zang; Jianyong Yu; Jianqin Lv; Ning Li; Jialing Zhang; Mingxiao Yang; Joey S. W. Kwong; Ran Pang; Jianfeng Wang; Zhengyu Cui; Yongpei Yu; et al. (BMC, 2023)
Abstract Background Hot flashes are the common and debilitating symptom among prostate cancer (PCa) patients undergoing androgen deprivation therapy (ADT). Strong evidence from multiple rigorously designed studies indicated that pharmacological option such as venlafaxine provides partial relief, but the tolerability is poor when dose is not tapered. Hence, alternative therapy is needed. Previous studies reported that acupuncture may be helpful in the management of hot flashes. However, the insufficient randomized controlled trial limited the quality of evidence. Methods Five hospitals will recruit 120 acupuncture naïve patients with moderate-to-severe hot flashes after prostate cancer received ADT in China from February 2023 to December 2024. Participants will be randomly 2:1:1 allocated to the 18 sessions of verum acupuncture at true acupuncture points plus usual care, 18 sessions of non-penetrating sham acupuncture at non-acupuncture points plus usual care, or usual care alone over 6 weeks. The primary outcome measure is the change of mean weekly hot flashes symptom severity score (HFSSS) at the end of treatment compared with baseline. Expected Results and Conclusion We will be able to measure the effectiveness of acupuncture for patients with PCa suffering from ADT-induced hot flashes and whether acupuncture is superior to sham acupuncture and usual care. The proposed acupuncture treatment might provide an alternative option for those patients. Trial Registration Clinicaltrials.gov (NCT05069467).